2005
DOI: 10.1088/0960-1317/15/7/017
|View full text |Cite
|
Sign up to set email alerts
|

Microreplication in a silicon processing compatible polymer material

Abstract: Devices combining optical and micromechanical elements have become key components for many applications in recent years. In this paper, we present a novel fabrication process for the integration of polymer micro-optical elements on silicon. The fabrication process relies on a reverse-order protocol in which the diffractive lens is first hot embossed into a polymer layer spin coated onto a silicon wafer and the subsequent process steps are carried out with the lens already in place. This is possible due to an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The resist pattern acts as the protective shield during the subsequent Cytop etch process, which was carried out in an inductively coupled plasma/reactive ion etch (ICP/RIE) system with the following etch conditions: 40.0 sccm O 2 , 90.0 mTorr chamber pressure, 200 W RF power and 0 W ICP power. A similar etch process is described in [22,23]. The etch rate of the Cytop polymer film was 1 µm min −1 for our etch conditions and the etch rate of the resist was approximately 0.3 µm min −1 .…”
Section: Formation Of Lensesmentioning
confidence: 88%
See 2 more Smart Citations
“…The resist pattern acts as the protective shield during the subsequent Cytop etch process, which was carried out in an inductively coupled plasma/reactive ion etch (ICP/RIE) system with the following etch conditions: 40.0 sccm O 2 , 90.0 mTorr chamber pressure, 200 W RF power and 0 W ICP power. A similar etch process is described in [22,23]. The etch rate of the Cytop polymer film was 1 µm min −1 for our etch conditions and the etch rate of the resist was approximately 0.3 µm min −1 .…”
Section: Formation Of Lensesmentioning
confidence: 88%
“…In previous work, we showed that it is possible to fabricate diffractive microlenses (sawtooth Fresnel lenses) by hot embossing of the Cytop polymer [22,23]. The new process presented here results in continuous-surface profile refractive lenses using the same polymer as a lens material.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, channels were formed by selectively etching away the polymer layer. This can be accomplished via patterned reactive ion etching, sacrificial liftoff, or physical milling. , As a result, hydrophobic polymer walls 500 nm thick defined the network of channels on the hydrophilic glass surface. The device was assembled by pressing the channel substrate face down onto the sensor surface to seal the channels.…”
Section: Methodsmentioning
confidence: 99%
“…This can be accomplished via patterned reactive ion etching, sacrificial liftoff, or physical milling. 21,22 The open-faced channel substrate was pressed against the sensor substrate forming a network of channels 500 nm in height. This was then positioned onto the SPRi prism for testing.…”
Section: Methodsmentioning
confidence: 99%